DESIGN AND IMPLEMENTATION OF A MICROCONTROLLER-BASED TEMPERATURE, HUMIDITY, AND PH MONITORING SYSTEM FOR HYDROPONIC GROWING MEDIA - Akhyar Muchtar; Andi Fitriati (Jurusan Pendidikan Teknik Elektro, 2023)
The current government is actively promoting the cultivation of horticultural crops as a means of cost savings, reducing air pollution, and environmental conservation. Due to the limited available land, the community has shifted to using hydroponic growing media. However, to ensure optimal plant growth, it is essential to implement a system that controls temperature, humidity, and the pH level of the nutrient solution in the hydroponic setup. This research employs an experimental methodology, leveraging temperature sensors, pH sensors, NodeMCU, and the Blynk application. The findings of this study demonstrate that to optimize the control of temperature, humidity, and pH levels of the nutrient solution, it is necessary to periodically add both pure water and nutrient solution. The addition of pure water alone to the nutrient solution in the growing media causes the pH to fluctuate by an average of 0.4 units per 1000mL of pure water added. Temperature and humidity control within the nutrient solution of the hydroponic media can be maintained by adding pure water. The study results showed that the temperature was controlled between 18°C and 25.2°C, with humidity levels ranging from 60% to 75%. The data processing time, from sensor data acquisition, data processing on the NodeMCU, to data transmission from NodeMCU to the Blynk application, averages 1.22 seconds. The command transmission time to execution varies from 30 seconds to 90 seconds, depending on the distance between the system and the growing media. This study concludes that the addition of pure water must be accompanied by the addition of nutrients to ensure that, alongside maintaining temperature and humidity, the pH level remains within the desired set point range.